Experimental Evidence of Rapidly Decaying Environmental DNA Highlights Infection Risk from Two Major Amphibian Pathogens - Joseph D. Trafford; Trenton W. J. Garner; David J. Murrell; Julia J. Day (Environmental DNA)
ABSTRACT Infectious diseases spread through international wildlife trade networks, presenting major conservation and welfare challenges. The diseases amphibian chytridiomycosis (caused predominantly by chytrid fungus Batrachochytrium dendrobatidis, Bd) and ranavirosis (caused by iridoviruses in the genus Ranavirus, Rv) are the result of infection by globally distributed pathogens. These pathogens spread internationally through live‐animal trade networks and have driven population declines, mass mortalities, and community collapse for a broad range of amphibian species. Environmental (e)DNA methods may provide highly sensitive and non‐invasive pathogen surveillance for traded or wild amphibians. To investigate the relationship between eDNA detection and environmental pathogen persistence, eDNA degradation rates were quantified across a range of temperatures (15°C–25°C) for both Bd and Ranavirus. Estimated decay rates suggest that overall pathogen eDNA concentration degrades by 99% between 18.9–52.4 h. Low levels of pathogen eDNA remained detectable for the duration of the experiment (> 28 days). Time was found to have a significant negative effect on eDNA concentration for both pathogens (p < 0.001). The negative effect of temperature on eDNA concentration was significant for both pathogens (20°C for Rv, p < 0.05; 25°C for Bd/Rv p < 0.001). We argue that high concentrations of eDNA represent viable pathogen in the environment, demonstrating the usefulness of eDNA for the monitoring of disease status of consignments of traded amphibians.